Peran Penting Orang Tua dan Lingkungan Sosial terhadap Kenakalan Remaja di Dusun Xix, Desa Sampali - Atika Rahayu; Fitri Armanda; Khaila Afsari; Liza Nur Fadillah; Thania Hermayanti Damanik (MODELING: Jurnal Program Studi PGMI, 2023)
The problem in this study is the importance of the role of parents and the social environment on juvenile delinquency in Sampali Village, precisely in XIX Hamlet, Sampali Village, Percut Sei Tuan District. This research is presented using descriptive qualitative research, namely observations to explore, interview or photograph how the problem situation of the community there will be studied thoroughly and in depth. This research was conducted in XIX Hamlet, Sampali Village, with resource persons consisting of several communities in XIX Hamlet to help collect information and data for this research. From the results of observations in Hamlet XIX, Sampali Village, Percut Sei Tuan District, it is known that there are several cases committed by local teenagers, namely drugs, brawls, and motorcycle gangs. After a deeper review, the researchers found out the reason why the teenager in Hamlet XIX, Sampali Village, Percut Sei Tuan District, did juvenile delinquency, namely because the teenager had a family that did not provide love and attention, a poor social environment, and weak self-control. Therefore, the role of parents is needed, such as building good relationships, instilling faith in the heart so that it becomes a stronghold in oneself so that it is not easy to fall into actions that are not commendable. If various solutions and coaching are carried out, it is hoped that the possibility of juvenile delinquency will decrease and be resolved. From the discussion on efforts to overcome juvenile delinquency, it should be emphasized that all efforts to control juvenile delinquency must be aimed at achieving a stable, harmonious, and mature adolescent personality. Adolescents are expected to become adults with strong personalities, physically and mentally healthy, firm in belief (faith) as a society, nation, and homeland.